2011
DOI: 10.3144/expresspolymlett.2011.58
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of mechanical properties of poly(vinyl chloride) with polymethyl methacrylate-grafted halloysite nanotube

Abstract: Halloysite nanotubes(HNTs) grafted with Polymethyl methacrylate(PMMA) were synthesized via radical polymerization. The properties of PMMA-grafted HNTs were characterized by transmission electron microscopy (TEM), fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA) and X-ray photoelectron spectroscopy (XPS). The results showed that PMMA grafted to the surfaces of HNTs successfully. Then, PVC/PMMA-grafted HNTs nanocomposites were prepared by melt compounding. The morphology, mechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
70
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(72 citation statements)
references
References 31 publications
1
70
1
Order By: Relevance
“…HNTs have recently gained considerable attention as a new type of nano-additive for enhancing the mechanical [13][14][15], thermal, crystallization [16,17], and fire performance of thermoplastic polymers, such as polypropylene and polyamide-6 [18], and thermosets, such as epoxy [19]. In recent years, the assembly of ordered metal nanoparticleson one-dimensional nanotubes to synthesize nanocomposites has attracted a great deal of attention in the field of electroanalytical chemistry; particularly in electrochemical sensors [20].…”
Section: Introductionmentioning
confidence: 99%
“…HNTs have recently gained considerable attention as a new type of nano-additive for enhancing the mechanical [13][14][15], thermal, crystallization [16,17], and fire performance of thermoplastic polymers, such as polypropylene and polyamide-6 [18], and thermosets, such as epoxy [19]. In recent years, the assembly of ordered metal nanoparticleson one-dimensional nanotubes to synthesize nanocomposites has attracted a great deal of attention in the field of electroanalytical chemistry; particularly in electrochemical sensors [20].…”
Section: Introductionmentioning
confidence: 99%
“…The functionalized HNTs have improved hydrophobicity and dispersibility in organic solvents. Liu et al [31] prepared modified HNTs by grafting the polymethyl methacrylate (PMMA) via radical polymerization and then compounding with poly (vinyl chloride) (PVC) to form composites with higher toughness, strength, and modulus. The results showed that the modified HNTs have uniform dispersed in PVC aqueous solution.…”
Section: Free Radical Modificationmentioning
confidence: 99%
“…A further difference between the layered silicatelike montmorillonite (MMT) and halloysite is the significantly lower cation exchange capacity (CEC) of HNT for modification via ionic exchange. However, in halloysite, nanocomposites with highly polar polymer contents [9][10][11][12], such as PVC [9,10], PA [11,12], or epoxy [13], require no modification/ treatment of the halloysite for the preparation of melt-mixed polymer nanocomposites with well distributed HNT. With non-polar polyolefins such as PP, due to the highly hydrophobic nature of PP, it is necessary to modify not only the halloysite [14][15][16][17], but also the polymer matrix to increase the polarity of PP [18][19][20][21].…”
mentioning
confidence: 99%